IMPLEMENTASI METODE DJIKSTRA DALAM MENENTUKAN JARAK TERPENDEK PADA PENDISTRIBUSIAN BARANG PT. AKUR MAKMUR - Haerul Anwar; Randi Kurnia Sandi; Adi Sukma (JURNAL REKAYASA SISTEM INDUSTRI, 2020)
PT. Akur Makmur needs the shortest distance solution for the process of distributing goods from theCentral Warehouse distribution to branches that need in the City quickly, this solution is needed toavoid congestion and speed in distributing goods, and djikstra in accordance with one of the methodsused to renew the shortest path so that the goods arrive on time. PT. Akur Makmur can minimize thecosts and time needed to distribute goods. The problems in this study are (1) How does PT. Make graphsin the form of graphs (2) How PT. Accurately determine the shortest distance using the djikstra method(3) Determine the costs that can be resolved if using the calculation results with the djikstra methodIn this study, taking real data in the field, then measuring the distance and time to use GoogleMaps facilities, then measuring the shortest distance using the djikstra algorithm, then compiling theroute of the data obtained and looking for the shortest path using the djikstra algorithm.Based on the results of this study, it can be concluded (1) determining the trajectory in the form ofa graphical algorithm (3) comparing the weight of each trajectory distance traversed in the distributionof goods (3) determining the shortest route to be used in the distribution of goods.Advice can be given to PT. Akur Makmur is as a comparison and alternative to the shortest pathchoice in the distribution of goods.